Mortalidade atribuível ao tabagismo no Brasil em 2003 - Paulo Cesar Rodrigues Pinto Correa (2007)
There are a number of methods for estimating smoking attributable mortality (SAM). Reliable estimates of SAM are essential for planning, funding and implementing anti-smoking programs successfully. We searched Medline and Lilacs databases for papers on SAM published up to October 20th, 2005 and analyzed the potential use of such methods in Brazil. We identified seven different methodological approaches to estimate SAM. The population attributable fraction method was first discussed by Levin in 1953. Doll & Peto used the excess mortality. Peto et al. proposed an indirect method that infers the prevalence of smoking by observing the excess rate of lung cancer mortality in the target population, as compared with an unexposed reference population. McAnulty et al. produced estimates of SAM using physician reports on death certificates. Sterling et al, Malarcher et al and Thun et al proposed three different methods of estimating SAM using relative risk estimates that were adjusted for potential confounding variables. Levins method, described more than 50 years ago, is the method adopted by an online application used in the United States since 1987. This online application is called Adult SAMMEC (Smoking-Attributable Mortality, Morbidity and Economic Costs). In the present work it was applied to estimate the smoking attributable mortality in 15 Brazilian capitals plus the Federal District in 2003. SAMMEC calculates ageadjusted SAM rates for persons aged 35 years and older. In order to be comparable, these rates were standardized to the age distribution of the Brazilian population in 2000. The 2003 Brazilian mortality data and smoking prevalence rates, combined with the American Cancer Societys Cancer Prevention Study II (CPS-II) cause and sex specific relative risks for smoking were also necessary to estimate SAM in these capitals. Prevalence of smoking were obtained from the National Survey on Risk Factors for Non Communicable Diseases, carried out by the Ministry of Health in 2002/2003. Cause, sex and age specific mortality statistics were obtained from the Brazilian Mortality System. The results indicate that in 2003, a total of 24,222 Brazilians (16,896 men and 7,326 women) died as a result of active smoking in the 16 Brazilian cities studied. Hence, cigarette smoking was responsible for 13.64% of deaths from all causes in the sixteen capitals in 2003 (18.08% among male deaths and 8.71% among female deaths). In 2003, the top four causes of adult smoking-related deaths were chronic airways obstruction (4,419 deaths), ischemic heart disease (4,417 deaths), lung cancer (3,682 deaths), and cerebrovascular disease (3,202 deaths). Cigarette smoking accounted for 419,935 years of potential life lost (279,990 for men and 139,945 for women) in the same year. The results, taken together with the annual Brazilian consumption of cigarettes per capita and the degree of social denormalization of cigarette smoking in Brazil, classifies the country at stage III in the tobacco pandemic model. Thus, public health policies to boost up smoking cessation treatments need to be reinforced. Moreover, smoke-free policies should become a priority in Brazil, as they lead to reductions in daily consumption of cigarettes and increases in tobacco use cessation and also prevent smoking initiation